Employee Experiences with a Newly Adopted Paid Parental Leave Policy: Equity Considerations for Policy Implementation - Dawn M. Richardson; Anna Steeves-Reece; Allea Martin; David A. Hurtado; Lisset M. Dumet; Julia M. Goodman (Mary Ann Liebert, 2019)
Purpose: Paid parental leave (PPL) policies offer immense opportunity to enhance health equity by providing financial stability to workers and promoting the health of families in the United States. Working in partnership with a local county government, which recently adopted a paid leave policy, we engaged in a qualitative substudy to enhance our understanding of how workers perceived and experienced the policy across levels of the socioecological framework. Methods: Working in partnership with Multnomah County, a large public-sector employer in Portland, OR that recently adopted a PPL policy, we collected qualitative data through focus groups with employees. Data were transcribed, coded, and analyzed thematically. Results: We conducted seven focus groups with county employees (N=35) in the fall of 2017. Three major themes emerged from the focus group data: intersectional inequities, disparities by department, and uneven benefits. Conclusions: Our findings highlight the inequities of experience with the PPL policy across employees at individual, organization, and environmental levels. These findings offer insight and guidance for entities considering the adoption and implementation of such policies to consider concrete steps to enhance equity of access and experience.